Confidence with text and reading performance using informational text - Basadre, Pier Angeli M. (The RAP Journal, 2010)
This study investigated the relationship between confidence with text and reading performance of grade 4 pupils using a 30-item Confidence with Text Questionnaire (CTQ) and reading performance tests using informational texts in both Filipino and English. Respondents were 30 public school pupils randomly chosen from five heterogeneous classes. The Spearman Rank-Order Correlation procedure was used to analyze the data. Results showed the subjects' level of confidence with text to be generally high; however, they need help in higher order thinking skills. A low correlation was found between the subject's confidence with text and reading performance using informational texts in both Filipino and English, though the subjects performed a little better in Filipino. The results imply that reading performance could slightly improve confidence with text given more frequent exposure to informational texts.